(untitled) (Journal on studies and research of academic knowledge, 2022)
The Basic Food Basket (CBA) is the set of foods that people require for their basic daily diet. In Encarnación, there is no scientific data on the composition of the CBA, demand and rotation, for which the diagnosis contributes to: decision-making, investments and other investigations. The purpose: to categorize the Basic Food Basket in the city of Encarnación, August-December/2021. The study is a categorize of exploratory type, mixed-predominant, transectional approach. The analysis units included nine (9) shopping centers selected for convenience. The key actors of each center answered the direct interviews about the indices of each indicator. Results: the CBA is composed of cereals and derivatives, oilseeds, dairy products, baked goods, fruit and vegetables and meat products; which, in the disaggregated, add up to forty-nine (49) articles of daily demand. With high demand: rice, sugar, milk, tomato, noodles, sunflower oil, fine salt, onion heads, cassava, felipe bread, wheat flour. Medium demand: beef, poultry, lettuce, spices, national orange, potato, green bell pepper and, with low demand: ham, Paraguay cheese, banana, beans, sandwich cheese and carrot. With the highest turnover are: rice, sugar, milk, tomato, noodles, sunflower oil, fine salt, onions, cassava, felipe bread and wheat flour. They have lower turnover, beef, poultry, lettuce, spices, national orange, potato, green bell pepper, ham, Paraguay cheese, banana, beans, sandwich cheese and carrot. The components were determined, the demand was identified and their rotation level was estimated.